Australian nursing students' knowledge and attitudes towards pressure injury prevention: A cross-sectional study. (May 2018) - Usher, Kim; Woods, Cindy; Brown, Janie; Power, Tamara; Lea, Jackie; Hutchinson, Marie; Mather, Carey; Miller, Andrea; Saunders, Annette; Mills, Jane; Zhao, Lin; Yates, Karen; et al.
Abstract: Aim: The aim of this study was to assess student nurses' knowledge of and attitudes towards pressure injury prevention evidence-based guidelines. Background: Pressure injuries are a substantial problem in many healthcare settings causing major harm to patients, and generating major economic costs for health service providers. Nurses have a crucial role in the prevention of pressure injuries across all health care settings. Design: A multi-centered, cross-sectional study was conducted using a paper-based questionnaire with undergraduate nursing students enrolled in seven universities with campuses across five Australian states (Queensland, New South Wales, Western Australia, Victoria and Tasmania). Methods: Data were collected from nursing students using two validated instruments (Pressure Ulcer Knowledge Assessment Instrument and Attitude Toward Pressure Ulcer Prevention Instrument), to measure students' pressure injury prevention knowledge and attitudes. Results: Students reported relatively low pressure injury prevention knowledge scores (51%), and high attitude scores (78%). Critical issues in this study were nursing students' lack of knowledge about preventative strategies to reduce the amount and duration of pressure/shear, and lower confidence in their capability to prevent pressure injury. Level of education and exposure to working in a greater number of different clinical units were significantly related to pressure injury prevention knowledge and attitude scores. Conclusion: The study findings highlight the need to implement a comprehensive approach to increasing Australian nursing students' pressure injury prevention and management knowledge, as well as ensuring that these students have adequate experiences in clinical units, with a high focus on pressure injury prevention to raise their personal capability.